Detección molecular del virus del distemper canino en casos clínicos de caninos domésticos no vacunados y evaluación de factores de riesgo - Soto R., Andrea (2018)
The canine distemper (CD) is a viral infection caused by a Morbillivirus of the family Paramyxoviridae. It can generate digestive, respiratory, and nervous symptomatology, depending on the infecting strain. This study was designed to detect the CD virus through the RT-PCR technique and perform the analysis of the data collected to have a current view of the behavior of this virus in Lima, Peru. Whole blood samples from 52 unvaccinated canines with clinical signs compatible with canine distemper were collected between June 2012 and January 2015. The nucleoprotein of 287 bp was successfully amplified in 32.7% (17/52) of the samples analyzed. In addition, it was found a greater detection of the virus, but not significative, in individuals that manifested systemic clinical signs (respiratory and digestive signs vs nervous) and within the age range of 1.5-4 months.